Implementation of Communicative and Action-oriented Approaches in Teaching French for Tourism for the Indonesian Public Level A1/A2 - Nurizki, Reza (LACULTOUR: Journal of Language and Cultural Tourism, 2023)
Teaching French as foreign language (FLE) in tourism polytechnic is unique. The NHI Bandung Polytechnic of Tourism aims to train young professionals in the three sectors of tourism: hotels, travel management and tourism management. The aim of teaching French at school is to provide basic knowledge of French and to train students to be able to use French in a professional environment. French lessons at NHI Bandung Polytechnic of Tourism are taught in a classic way and focus on the grammatical aspect rather than on the communicative function. The problem of the lack of interactivity between the students and the teacher is considered as a hypothesis of the research. It is necessary to carry out an active pedagogy to invite the pupils to react during the lesson, to push them to participate. Based on this reflection, the author therefore decided to set up active pedagogy by using the communicative and action-oriented approach in the teaching of professional French for tourism